Neuroanesthesia Management in Transspenoidal Pituitary Cyst Surgery - Subagyo, Houdini Pradanawan; Nofiyanto, Eko (Journal of Anaesthesia and Pain, 2024)
Background: Neuroanesthesia management of patients with masses in the sella area undergoing transspenoidal surgery is a challenge for anesthesiologists. Good preoperative, intraoperative and postoperative management is shown to improve the patient’s quality of life.Case: A 45-year-old man with chief complaints of headache and visual disturbances, from the results of the vision examination obtained visus 1/60 (count fingers) and narrowed visual field area. From computerized tomography (CT) scan and Magnetic resonance imaging (MRI) images of the Head obtained a picture of cystic mass of the suprasellar sella pressing the optic chiasm. The patient was planned for surgical excision of pituitary cyst per transspenoidal. The patient underwent general anesthesia with endotracheal intubation with intravenous induction fentanyl, propofol, atracurium and lidocaine, followed by maintenance with sevoflurane inhalation agent with 60% oxygen. During the operation the hemodynamic condition was stable and postoperatively the patient was extubated in the operating room and then treated in the intensive care unit.Conclusion: In pituitary cyst patients undergoing transspenoidal surgery, the preoperative evaluation is mainly aimed at airway assessment, neurological disorders and hormonal disorders in patients. During intraoperative, the anesthesiologist is expected to optimize cerebral oxygenation, maintain hemodynamic stability, facilitate the surgical area, prevent and manage intraoperative complications and rapid recovery of consciousness. Postoperatively a good neuroendocrine evaluation is required